A Novel Animal Model of Impaired Glucose Tolerance Induced by the Interaction of Vitamin E Deficiency and 60Co Radiation. (14th April 2015) - Guan, Yue; Cheng, Yan; Yin, Ying; Duan, Jialin; Wei, Guo; Weng, Yan; Guo, Chao; Zhu, Yanrong; Wang, Yanhua; Xi, Miaomiao; Wen, Aidong
Abstract : Impaired glucose tolerance (IGT), known as the prediabetes stage, is usually induced by habits of life or environmental factors. Established IGT animal models are mostly conducted with chemical compounds such as streptozocin or genetic modification. However, the occasion of exposure to these factors in daily life is seldom. The objective of this study was to establish a new animal model of IGT induced by VE deficiency in diet and exposure to radiation. SD rats were treated individually or in combination of these two factors. In the combination group, the calculated insulin sensitivity index decreased; then HOMA- β value increased. Oxidative damage and IGT were observed. Insulin secretion level in perfusate from pancreas response to glucose was characterized by a rapid but reduced first phase and an obviously defective second phase upon pancreas perfusion. Histopathological images demonstrated the pathological changes. Western blotting analysis showed that the insulin signaling pathway was downregulated. The interaction of VE deficiency in diet and exposure to radiation could break the equilibrium of oxidation and antioxidation and result in IGT. More importantly, a new IGT model was successfully established which may be conducive to further research into development of drugs against human IGT.